2020
DOI: 10.1007/978-3-030-33208-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Biological Clocks and Rhythms in Polar Organisms

Abstract: Biological clocks are universal to all living organisms on Earth. Their ubiquity is testament to their importance to life: from cells to organs and from the simplest cyanobacteria to plants and primates, they are central to orchestrating life on this planet. Biological clocks are usually set by the 'beat' of the day-night cycle, so what happens in polar regions during the Polar Night or Polar Day when there are periods of 24 hours of darkness or light? How would a biological clock function without a time-keepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Given that in 2013 and 2022, data were collected during the "day" (08.45 -17.00 UTC) and "night" (00.10 -04.00 UTC) periods (Table 1), respectively, the second hypothesis proposes an interpretation of the results, taking into account the possible Diel Vertical Migration (DVM) of medium-size fish. Previous studies (Falk-Petersen et al, 2008;Last et al, 2020;Pettitt-Wade et al, 2021) have confirmed that biological clocks of marine organisms are important for shaping their daily activities at high latitudes, and there are some confirmations that organisms could perform DVM in the Arctic during the Polar Night or Polar Day.…”
Section: The Difference In Depth Distributions Of Ts Of Middle-size F...mentioning
confidence: 90%
“…Given that in 2013 and 2022, data were collected during the "day" (08.45 -17.00 UTC) and "night" (00.10 -04.00 UTC) periods (Table 1), respectively, the second hypothesis proposes an interpretation of the results, taking into account the possible Diel Vertical Migration (DVM) of medium-size fish. Previous studies (Falk-Petersen et al, 2008;Last et al, 2020;Pettitt-Wade et al, 2021) have confirmed that biological clocks of marine organisms are important for shaping their daily activities at high latitudes, and there are some confirmations that organisms could perform DVM in the Arctic during the Polar Night or Polar Day.…”
Section: The Difference In Depth Distributions Of Ts Of Middle-size F...mentioning
confidence: 90%
“…It is not unreasonable to suppose that in M. sanguinea a similar repertoire of entrained biological rhythms may exist, as has been demonstrated in other large polychaetes with a large supra-oesophageal ganglion and well-developed sensory system, but more amenable to experimental investigation (Watson et al ., 2000a; Last and Olive, 2004; Olive et al ., 2005); notably in Platynereis dumerilli (Audouin and Milne Edwards, 1883), which has become the standard polychaete genomic model (Zantke et al ., 2014). Such biological rhythms are also observed in diverse geographic regions (Last et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of light decreases exponentially with depth and can restrict the productivity of photosynthetic organisms like seagrasses and coral symbionts (Duarte, 1991; Kahng et al, 2019; Lesser et al, 2021). Light can also constrain latitudinal shifts because highly seasonal diel cycles lead to reduced nutrient availability and limited opportunities for visual foraging in the winter (Chen & Wang, 2016; Last et al, 2020; Ljungström et al, 2021).…”
Section: Discussionmentioning
confidence: 99%